2020
DOI: 10.2174/1567201817666200102125242
|View full text |Cite
|
Sign up to set email alerts
|

Development and In vitro Evaluation of Nifedipine Gel Formulations for Anorectal Applications

Abstract: Objective: Current study focuses on the formulation and characterization of lipophilic and hydrophilic gel formulations of nifedipine to treat anal fissure via anodermal application. Methods: Lipophilic gels were prepared with Aerosil grades as gelling agents in bulk oils. Polyethylene glycols, hydroxypropyl methylcellulose, and Carbopol® 974P were used as gelling agents in water and propylene glycol for forming hydrophilic gels. The effect of repeated Freeze-Thaw Cycles (FT-C) on microstructures of the gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Some studies argued that the results of freeze-thaw testing for six cycles able to predict the physical stability of shelf life. 22 Therefore, formula 1 can be concluded that the formula is the most stable and is predicted to has a longer shelf life than another formula. Moreover, phase separation of the gel product is one possible reason for a high variation of assay results from content uniformity test.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies argued that the results of freeze-thaw testing for six cycles able to predict the physical stability of shelf life. 22 Therefore, formula 1 can be concluded that the formula is the most stable and is predicted to has a longer shelf life than another formula. Moreover, phase separation of the gel product is one possible reason for a high variation of assay results from content uniformity test.…”
Section: Discussionmentioning
confidence: 99%